2011
DOI: 10.1007/s10815-011-9582-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological pH buffers in IVF: help or hindrance to success

Abstract: Purpose Minimizing environmental stress helps maintain cellular homeostasis and is a crucial component in optimizing embryo development in vitro and resulting ART success. One stressor of particular interest is pH. Biologic buffers, such as HEPES and MOPS, are valuable tools for stabilizing pH. The objective of this manuscript is to summarize efficacy and impact of various pH buffers used during IVF lab procedures Methods Keyword searches were performed using Pubmed and Medline and relevant literature reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 102 publications
(191 reference statements)
0
50
0
1
Order By: Relevance
“…Analysis of pH revealed a significant difference in pH values of KSOMeq at 37°C in comparison with the the rest of treatments. These findings demonstrated that cryotubes allow CO 2 difussion into the air and a concomitant basification that was not buffered by the presence of HEPES as in KSOM-H, and that this diffusion was potentiated by temperature [17]. More efficient ways to preserve storage environment have been reported [18], that should be considered as an alternative if transport has to take place under such conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of pH revealed a significant difference in pH values of KSOMeq at 37°C in comparison with the the rest of treatments. These findings demonstrated that cryotubes allow CO 2 difussion into the air and a concomitant basification that was not buffered by the presence of HEPES as in KSOM-H, and that this diffusion was potentiated by temperature [17]. More efficient ways to preserve storage environment have been reported [18], that should be considered as an alternative if transport has to take place under such conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is not unreasonable to conclude that ART intervention during the periconception period might induce a health risk in the resulting offspring. During ART, specifically in vitro gamete manipulation and embryo system, spermatozoa, oocytes, and embryos are exposed to various nonphysiological factors, such as culture media, altered pH [51], light [52,53], higher oxygen pressure [54], increased concentration of reproductive hormones [55], and mechanical injection or biopsy, all of which contribute to an altered periconception environment [56]. In addition to in vitro ART, a sub-optimal uterine environment following embryo transfer is thought to further influence the long-term viability of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…There are many possible ways to improve our freezing system, such as changing the base medium from PBS to a 1:1 mixture of PBS and HEPES, as this mixture is known to stabilize pH better than PBS alone at low temperatures [37]. Antioxidants could also be added to the freezing and thawing media, as cryopreservation can generate reactive oxygen species that are harmful to cells [38].…”
Section: Discussionmentioning
confidence: 99%